Examining the Assistance Needed by Prison Students to Succeed in their Distance Education Studies - Mahlangu, Vimbi Petrus (Research in Social Sciences and Technology, 2025)
This study investigates the educational experiences of twelve jailed students in prison in Namibia, with a specific emphasis on identifying the factors necessary for their academic achievement. The study aimed to gain a deeper understanding of the jailed students' perspectives on the impact of education, utilizing audio-recorded interviews. The interviews were meticulously transcribed verbatim by an English-speaking transcriber to ensure the utmost accuracy and thoroughness in documenting the participants' narratives. The author employed an interpretive paradigm to analyze and delve into the subjective meanings and experiences of the pupils. This methodology enabled a comprehensive understanding of the influence of educational programs on the lives of jailed inmates, potentially aiding in their rehabilitation and successful reintegration into society. The findings offer unique insights into the significant influence that education may have in correctional settings, revealing the challenges and accomplishments encountered by incarcerated students. This study contributes to the broader discourse on education in prisons by focusing on the real-life experiences of prisoners. It highlights the need to provide jailed individuals educational opportunities to facilitate their personal and professional development. This study emphasizes the significance of tailored educational interventions in prisons to foster advantageous outcomes for incarcerated persons and society.